Cancer profiles by affinity propagation - Ambrogi, Federico; Raimondi, Elena; Soria, Daniele; Boracchi, Patrizia; Biganzoli, Elia M. (2008)
The affinity propagation algorithm is applied to a problem of breast cancer subtyping using traditional biologic markers. The algorithm provides a procedure to determine the number of profiles to be considered.